PENGARUHHJLINGKUNGANHJKELUARGA, HJLINGKUNGANHJTEMANHJSEBAYAHJDANHJMOTIVASIHJEKONOMI TERHADAPHJMINATHJMENGIKUTIHJPPGHJ(STUDIHJPADAHJMAHASISWAHJPENDIDIKANHJEKONOMI, PENDIDIKANHJAKUNTANSIHJDANHJPENDIDIKANHJADMINISTRASIHJPERKANTORANHJ2014/2015 - -, hjFauzia Liana Utama -; -, Bambang Wasito Adi -; -, Sunarto - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
This research aims test the influence (1) family environment towards interest to follow PPG on students, (2) peer environment against student interest to follow PPG on students, (3) economic motivation on student interest to follow PPG on students. The population in this research are students of Economic Education, Accounting Education and Office Administration Education on 2014/2015 at FKIP UNS which amounted to 170 students. Samples in this study as many as 63 respondents taken with Proportional Random Sampling technique. This research used quantitative method with explanatory survey. The data were collected by questionnaire  and documentation technique analysis. The results of this research are: (1) There is a  positive and  significant  influence of family environment on the interest to joining PPG. (2) There is a positive and significant influence of peer environment  on the  interest to joining PPG. (3) There is a positive and significant influence of economic motivation on the interest to joining PPG. (4) There is a positive and significant influence of family environment, peer environment, and economic motivation to the interest to joiningPPG.The relative contribution of the family environment is 20.8%,the peer environment  is 59.6% and the economic motivation is 19.6%of the interest to joining PPG. Meanwhile, effective contribution of family environment variable equal to 15,59%, peer environmental variable equal to 44,51%, and economic motivation variable equal to 14,59% to interest to joining PPG